Os olhos são cegos: comunicação institucional interligada à representação social em fotolivro para Fundação Dorina Nowill para Cegos. - EVERTON, Mary Aurea de Almeida Costa (2021)
Communication is one of the main variables the occurrence of inclusion of the visually impaired person, because when a favorable communication environment is built, they begin to have basic conditions for participation in society. social representation about the blind, through the attributes of the Dorina Nowill Foundation for the blind.